Implementation of Business Trade Licensing Service (Study on Investment Agency and One-Door Integrated Service of Tulungagung Regency) - Laily Miftahur Rohmah; Siti Rochmah; Riyanto Riyanto (Wacana: Jurnal Sosial dan Humaniora)
Public service is a public bureaucracy product accepted by society widely. One kind of public bureaucracy product is the Business Trade License, which has a certain quality as one of the supporting factors that motivates the creation of economic growth through better trade and service business. This study aims to find out and describe the implementation of a door-integrated service in Tulungagung. The Investment Agency and One-Door Integrated Service (DPM and PTSP) of Tulungagung Regency are necessary to improve business trade licensing services. The research method used in this research was qualitative. Based on the Regulation of Tulungagung Regency, the Regent carried out the principles: Coordination meant coordination among the organization members so that cooperation was created in giving business trade licensing service to the society. Synchronization in the implementation of business trade licensing service at DPM and PTSP of Tulungagung Regency was realized through the clear task division in the organization based on each field. Good integration among the organization's members would achieve the purpose of the organization. Security and Certainty meant that implementing business trade licensing service had to be based on the rule of law that, was the Regulation of Tulungagung Regency Regent No 76/2014. On the other hand, Certainty meant Certainty related to the procedure and the implementation of business trade licensing service.